Faktor-Faktor Penyebab Kurangnya Pengamalan Nilai-Nilai Pancasila Dalam Sikap Dan Prilaku Siswa di SMPN 7 Muara Bungo - Arisman Sabir (LP3M STKIP Muhammadiyah Muara Bungo, 2023)
This research is a qualitative research using descriptive method which aims to find out the factors causing students' lack of awareness in practicing Pancasila values and the school's efforts to instill students' awareness in practicing Pancasila values. The informants were school principals, deputy principals, PKN teachers, counseling teachers, school administration staff and students. Data collected by observation, interviews and documentation. Test the validity of the data using data triangulation. Data analysis techniques: data collection, data reduction, data presentation, and conclusions. The results showed that the factors causing the lack of practicing Pancasila values in students' attitudes and behavior were: (1) The students themselves, the lack of awareness of students about the importance of practicing Pancasila values. (2) peers, there is influence from fellow students who behave negatively. (3) Schools, inadequate school facilities. (4) Family, lack of parental attention. Efforts made by schools to instill students' awareness of practicing Pancasila values in schools are: (1) conducting socialization, so that all parties know the importance of practicing Pancasila values, especially for students and parents. (2) providing exemplary and understanding of Pancasila, setting an example of good behavior to students and so that the understanding of Pancasila values can be carried out properly. (3) provide guidance and direction, in order to be able to find solutions to problems that students do. (4) giving punishment, in order to give a deterrent effect to students.